An encryption method based on computational ghost imaging with chaotic mapping and DNA encoding. (1st June 2022) - Yang, Zhongzhuo; Yuan, Sheng; Li, Jinxi; Bai, Xing; Yu, Zhan; Zhou, Xin
Abstract: An encryption method based on computational ghost imaging (CGI) with chaotic mapping and DNA encoding is proposed. To reduce the amount of keys in the CGI-based encryption system, the chaotic mapping algorithm is used to generate the random sequence as the speckle measurement matrix of CGI system. The measurement data of the bucket detector is subjected to block and DNA operations, which introduce the nonlinear characteristics in the encryption process. The problem of linear vulnerability of the encryption system has been greatly improved. Numerical simulation results show that, compared with the traditional CGI-based encryption method, the proposed method greatly reduces the amount of keys, increases the key space and enhances the security of the system.